Prognosis in current heart failure patients - Alba, Ana C. (My University, 2014)
Background: Heart failure (HF) constitutes an important growing medical and economic problem with high prevalence and mortality. Prognosis assessment remains a challenge because of the dynamic nature of HF and the existence of some unexplained variation in outcomes. Our objective was to refine the process of prognostic assessment in current HF patients.
Methods: We conducted a systematic review to identify existing risk prediction models in ambulatory HF patients, a meta-analysis to identify mortality predictors in HF patients treated with an implantable cardioverter defibrillator (ICD), a retrospective cohort study to validate a new model, the HF Meta-Score, derived from the results of the meta-analysis and a cross-sectional and prospective cohort study to evaluate whether circulating progenitor cells (CPCs) are associated with functional capacity and mortality in ambulatory HF patients.
Results: We identified 20 risk prediction models in ambulatory HF patients; only five were externally validated showing limited discrimination and calibration. The two most validated models were derived from HF cohorts from the 1990s and reported limited performance in ICD patients. In a meta-analysis, we identified that age, baseline renal function, history of heart failure, chronic obstructive pulmonary disease, diabetes, peripheral vascular disease, left ventricular ejection fraction, NYHA class, atrial fibrillation, wide QRS and the occurrence of appropriate or inappropriate ICD shocks were independent mortality predictors. Some of these predictors were omitted in previously identified models. From the results of the meta-analysis, we developed the HF Meta-Score that showed better performance that an existing model. We observed that CPCs were independently associated with functional capacity and outcomes in ambulatory HF patients.
Conclusions: These results open many pathways to further refine the prognostic assessment in ambulatory HF patients. The HF Meta-Score is a promising score. The clinical utility of the HF Meta-Score and of the incorporation of new predictive factors, such as CPCs, needs to be tested.
Keywords: Heart failure; prognosis; survival; circulating progenitor cells; implantable cardioverter defibrillator; Cardiology; Cardiovascular Diseases; Cardiology